Effect of Fertilizer Management on NPKS Leaching Loss from Sandy Loam Soil under Alternate Wetting and Drying Condition (Bangladesh Rice Journal, 2016)
Leaching loss of nutrients hampers plant growth and contributes to environmental pollution. An experiment was conducted at the net house of Soil Science Department, Bangladesh Agricultural University, Mymensingh during January to May 2009 to find out the leaching loss of N, P, K and S from sandy loam soil. Each pot received 6.67 kg dry soil with an opening at the bottom for collecting leachates. Six treatments were used: T0 = control, T1 = NPKS (120, 25, 60 and 20 kg ha-1), T2 = NPKS (180, 37, 90 and 30 kg ha-1), T3 = NPKS (90, 5, 28 and 17 kg ha-1) + cowdung (2.5 t ha-1), T4 = NPKS (109, 25, 60 and 20 kg ha-1, N as USG) and T5 = as T1 but N applied as foliar spray. Treatments were arranged in a completely randomized design with three replications. Leachates were collected at 15 days interval for determination of NPKS. The total leaching loss of N, P, K and S due to different treatments ranged from 16.00 to 90.21, 0.07 to 0.29, 9.60 to 11.20 and 3.75 to 17.81 kg ha-1, respectively. Application of chemical fertilizer at higher rates resulted in greater loss of nutrients. Integrated fertilizer management with cowdung (T3) minimized such losses. Use of USG also reduced leaching loss of N, P, K and S. The application of cowdung and USG with recommended balanced fertilizer might be useful for minimizing N, P, K and S loss from wetland rice field.Bangladesh Rice j. 2016, 20(1): 59-64